Effectiveness and safety of PD-1/PD-L1 inhibitors in advanced or recurrent endometrial cancer: a systematic review and meta-analysis - Han, Songfei; Guo, Cuishan; Song, Zixuan; Ouyang, Ling; Wang, Yizi (Frontiers in Pharmacology, 2023)
Abstract Background: Studies in recent years have shown that PD-1/PD-L1 inhibitors may have better effectiveness in patients with advanced or recurrent endometrial cancer. The effectiveness of PD-1/PD-L1 inhibitors is thought to be related to mismatch repair-deficient (dMMR) and mismatch repair-proficient (pMMR) classification in advanced or recurrent endometrial cancer. This study aims to evaluate the effectiveness of PD-1/PD-L1 inhibitors in patients classified as dMMR and pMMR. Methods: Medical databases were searched to identify relevant publications up to November 30, 2022. The primary outcome was comparison of objective response rate (ORR) in patients with dMMR and pMMR following treatment with PD-1/PD-L1 inhibitors; secondary outcomes were single-group ORR in patients with dMMR and in patients with pMMR, respectively. Results: Eleven studies were eligible for analysis and patients with advanced or recurrent endometrial cancer with molecular classification of dMMR had a higher total ORR than those with pMMR (odds ratio [OR], 7.70; 95% confidence interval [CI], 3.22–18.38; p < 0.01), with low evidence of between-study heterogeneity (I2 = 0%). The total ORR of patients with advanced or recurrent endometrial cancer with molecular type dMMR was 51.9% (95% CI, 33.6–69.9%). The overall ORR of patients with advanced or recurrent endometrial cancer with molecular type pMMR was 16.1% (95% CI, 5.5–30.3%). Conclusion: In our including studies, the patients with advanced or recurrent endometrial cancer with molecular types of dMMR and pMMR, following treatment with PD-1/PD-L1 inhibitors, the total ORR of patients with dMMR was higher than that of patients with pMMR. Since the current number of studies is not very large, it is possible that more studies will be published in the future and more precise results will be discussed further. Key words: endometrial cancer, PD-1 inhibitors, PD-L1 inhibitors.